Toksisitas Subkronik Gelatin Kulit Ikan Patin Siam (Pangasius hypophthalmus) Terhadap Mencit (Mus musculus) - Novalia Rachmawati; Radestya Triwibowo; Ajeng Kurniasari Putri (Balai Besar Riset Pengolahan Produk dan Bioteknologi Kelautan dan Perikanan, 2011)
ABSTRACT Gelatin from catfish (Pangasius hypophthalmus) skin had been produced by Research Center for Marine and Fisheries Product Processing and Biotechnology. To determine the safety of thegelatin, a subchronic in vivo toxicity study had been done on mice. The study used male mice (Mus musculus) with 20–30 g body weight each. Gelatin was given orally by gavage once a day. Mice were divided into 4 groups of treatment. The doses given were 0 (negative control) 1.5; 3 and 6% of gelatin which was equal to 0, 12, 24 and 48 mg/g of mice body weight. The study had been conducted for 4 weeks and continued for 2 weeks of recovery phase. Blood serum condition, i.e. Glutamic Oxaloacetic Transaminase (GOT), Glutamic Pyruvic Transaminase (GPT), creatinine, albumine and Blood Urea Nitrogen (BUN) and organ (liver, kidney, stomach) damage were investigated. The results showed that gelatin at the highest dose (48 mg/g bw of mice) gave asignificant effect on GOT level at the second week of treatment. Furthermore, there was no significant effect of treatments on organ damage level.